Construction and Validation of a Necroptosis-Related Signature Associated With the Immune Microenvironment in Liver Hepatocellular Carcinoma - Wang, Gongjun; Ding, Baoning; Sun, Libin; Guo, Jing; Wang, Shasha; Li, Wenqian; Zhang, Yuqi; Lv, Jing; Qiu, Wensheng (Frontiers in Genetics, 2022)
Background: Liver hepatocellular carcinoma (LIHC) is a widespread and often deadly neoplasm. There is increasing evidence that necroptosis mediates numerous tumor-associated behaviors, as well as the regulation of the tumor microenvironment, suggesting its use as a biomarker for tumor prognosis. Methods: Data on mRNA expression and necroptosis regulators were acquired from the TCGA and KEGG databases, respectively. Unsupervised cluster analysis was performed on LIHC patients together with necroptotic regulator expression and differentially expressed necroptosis-related genes (DENRGs) were acquired by comparing the two clusters. The signature based on eight DENRGs was constructed and verified through independent data sets, and its relationship to the tumor microenvironment was investigated. Results: The unsupervised cluster analysis based on the expression of necroptotic regulators demonstrated inherent immune differences among LIHC patients. In all, 1516 DENRGs were obtained by comparison between the two clusters. In the training set, the final eight genes obtained by univariate, LASSO, and multivariate Cox regression were utilized for constructing the signature. The survival and receiver operating characteristic (ROC) curve achieved satisfactory results in both sets. The high-risk group was characterized by greater immune infiltration and poor prognosis. The results of survival analysis based on the expression of eight DENRGs further confirmed the signature we established. Conclusion: We established and validated a risk signature based on eight DERNGs related to the tumor microenvironment. This provides a possible explanation for the different clinical effects of immunotherapy and provides a novel perspective for predicting tumor prognosis in LIHC.